The digital photography book : the step-by-step secrets for how to make your photos look like the pros'! Part 5, Photo recipes - Kelby, Scott (2015)
In parts 1 through 4 of this series, the most popular chapter in the book has always been the last chapter: "Photo Recipes to Help You Get 'The Shot'." In each of those chapters, Scott shows a final image and then describes how to get that type of shot. Here, in part 5, he gives you what you've been waiting for: an entire book of nothing but those amazing photo recipes. But, he took it up a big notch by adding a behind-the-scenes photo for every single recipe. Now you can see exactly how it was done, so you can get that exact same look every time. In these extra pages, each spread allows you to dig in a little deeper and really unlock the power of these recipes. Scott breaks each spread into four segments: (1) he explains exactly what you're seeing behind the scenes, (2) he lists all of his camera settings, and lens and lighting info--it's all there, (3) he gives you his thought process, so you learn exactly why he does it this way, and (4) he shares all the post-processing in Lightroom or Photoshop that goes on after the shoot.
Includes index.
Keywords: Photography -- Digital techniques; Photography -- Digital techniques